Pancreatic MicroRNAs in Ictidomys tridecemlineatus Associated with Metabolic Diseases: Nature’s Insights into Important Biomarkers - Olawale O. Taiwo; Saif Rehman; Kenneth B. Storey (Biomolecules)
Hibernation involves a profound metabolic rate depression (MRD) that enables certain species to survive prolonged periods of low energy availability. The thirteen-lined ground squirrel uses MRD to arrange cellular and biochemical pathways which suppress nonvital genetic and cellular pathways to conserve internal energy while preserving all essential processes. This study investigates the role of microRNAs (miRNAs) in controlling key signaling pathways and cellular processes in pancreatic tissue during hibernation. Using next-generation sequencing and broad genomic analysis, we analyzed and identified seven differentially expressed miRNAs (miR-29a-3p, miR-22-3p, miR-125-5p, miR-200a-3p, miR-328-3p, miR-21-5p, and miR-148-3p) in the pancreas of hibernating 13-lined ground squirrels (Ictidomys tridecemlineatus). Our findings reveal that these miRNAs regulate pathways involved in glucose homeostasis, including insulin secretion and metabolic regulation, contributing to the unique adaptations of hibernation. These insights advance our understanding of the molecular adaptations underlying hibernation and may have implications for therapeutic strategies targeting metabolic disorders such as diabetes.